Proposal of a study protocol of a preliminary double-blind randomized controlled trial. Verifying effects of selenium supplementation on selenoprotein p and s genes expression in protein and mRNA levels in subjects with coronary artery disease: selenegene - Gharipour, Mojgan; Sadeghi, Masoumeh; Behmanesh, Mehrdad; Salehi, Mansour; Roohafza, Hamidreza; Nezafati, Pouya; Khosravi, Elham; Hosseini, Mohsen; Keshvari, Mahtab; Rouhi-Bourojeni, Hojat; Sarrafzadegan, Nizal (Acta Biomedica Atenei Parmensis, 2019)
Background: Selenium is the component of selenocystein amino acid, which itself is the building block of selenoproteins having diverse effects on various aspects of the human health. Among these proteins, selenoprotein P is the central to the distribution and homeostasis of selenium, and selenoprotein S as a transmembrane protein is associated with a range of inflammatory markers, particularly in the context of cardiovascular disease. It is known that selenium status outside of the normal range is considered to confer different benefits or adverse cardiovascular risk factors. Therefore, for the first time, we aimed to verify effects of Selenium supplementation on Selenoprotein P and S Genes Expression in Protein and mRNA Levels in Subjects with Coronary Artery Disease (CAD). Methods: This is the study protocol of a double blinded randomized clinical trial on 130 subjects with angiographically documented stenosis of more than 75% in one or more coronary artery vessels. In this 60-day study, 65 patients in each group received either a 200mg selenium yeast or placebo tablets once daily. During the study, subjects were followed by phone calls and visited our clinic twice to repeat baseline measurements. We hypothesized that our finding would enable a more basic and confirmed understanding for the effect of selenium supplementation by investigating its effect on gene expression levels in people with CAD. Discussion: Upon confirmation of this hypothesis, the beneficial effect of inflammation regulation by supplementation with micronutrients could be considered for subjects with CVD.